An Analysis of the Financial Situation of Central Units of Group Purchasing Organizations - Zimon, Grzegorz (International Review of Management and Marketing, 2019)
Small enterprises start to cooperate with each other in order to improve their financial situation. They combine to create various types of multi-entity organizations such as group purchasing organizations (GPOs). This is to provide enterprises with an improved financial performance and operational safety in the market. In general, enterprises operating within GPOs are managed by a specially created company which can be defined as a central unit. It is responsible for the flow of supplies, cash, information on the producer - company line. In order such transactions could be carried out efficiently, the central unit must have a stable financial position. The aim of the article is to assess the financial situation of central units of selected purchasing groups. The research conducted showed that the central units had a stable financial situation. Their activity is profitable. The only disadvantage that can be observed is low financial liquidity. For the safe operation of the central units, it is necessary to maintain a faster rotation of receivables in days from the rotation of liabilities towards suppliers on days. This will allow the purchasing group’s central unit to function safely in the market Keywords: central unit, group purchasing organizations, financial situation JEL Classifications: G30; G33; L15 DOI: https://doi.org/10.32479/irmm.8061